(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Environmental factors play a critical role in the efficiency of poultry farming, affecting the health, productivity, and welfare of the birds. Key parameters such as temperature, humidity, ventilation, lighting, and housing conditions must be meticulously managed. Temperature control is vital to prevent heat stress, which can decrease feed intake and growth rates, while optimal humidity and ventilation are necessary to maintain air quality and prevent respiratory diseases. Proper lighting regimes and adequate housing conditions, including space allocation and litter quality, also significantly impact growth and reproductive performance. Effective biosecurity measures further ensure disease prevention and overall flock health. Optimizing these environmental factors is essential for maximizing poultry farming efficiency, enhancing economic outcomes, and promoting sustainable practices. 110 people were chosen favourably for this investigation. Convenience sampling method was used to gather 110 respondents from Kanyakumari district poultry farming owners in order to obtain the relevant data.